Hábitos de postura de Piezodorus guildinii em soja - Link, Dionisio; Concatto, Luiz Carlos (Revista do Centro de Ciências Rurais, 2008)
Um estudo da oviposição de Piezodorus guildinii em soja, durante a safra 1977/78, foi realizado em Santa Maria, RS. O número médio de ovos/postura foi de 17,47. A variação foi de 4 a 39 ovos por postura. A maioria das posturas ficou localizada nas vagens. Os valores de ninfas e parasitas emergidas foram de 46,4 e 17,7% respectivamente. Telenomus mormideae Costa Lima (Hymenoptera, Scelionidae) foi o parasito dor ovos. Não foram encontradas posturas em plantas com menos de 30 cm de altura, acamadas ou muito densas. No interior das plantas as posturas ficaram no mínimo a 10 cm do nível do solo. Abstract A study of the oviposition of Piezodorus guildinii on soybean plants, was made at Santa Maria, RS, during the crop year 1977/78. The mean number of eggs per mass from 542 egg masses was 17.47 and the number of eggs per mass was between 4 and 39. The pods were the main oviposition site. The nymphs and parasites emerged were 46.4 and 17.7% respectively of the eggs collected. Telenomus mormideae Costa Lima (Hymenoptera, Scelionidae) was the egg parasite. The oviposition occurred on plants above 30 cm of height. The lodging and high density population of soybean plants were unfavorable for oviposition. There were no egg masses under 10 cm above the ground leve1 in the soybean plant.